Cost Efficiency Analysis in UK Banking Sector - xiang, zhoupei (2019)
This study analyzes the cost efficiency level and its determinants of 36 commercial banks in the UK from 2011 to 2018 under the government's increasing supervision. The results show that the cost efficiency of the UK banking industry varies widely from 15% to 98%, but the overall industry average efficiency level has improved and continued to develop since 2011. From the perspective of determinants, bank size is positively correlated with cost efficiency and negatively correlated with profitability, loan quality and liquidity. However, economic growth and inflation are not related to the efficiency of the banking industry. Overall, this reflects the improvement in financial stability and operational quality of the UK banking sector in the later stages of financial crisis regulation. However, under the high requirements of fund supervision, there are still a large number of monopolistic commercial banks facing the problem of large reform costs and difficulty in improving their operational level in the short term. Keywords: cost efficiency, stochastic frontier analysis, UK banking sector